Developing the Guidelines for Fabrication of Laboratory Prototype Voltage Source Converters - Chandrasena, Ruwan Pathiranage Sarath; Barbieri, F.; Shahnia, Farhad; Ghosh, Arindam; Rajakaruna, Sumedha (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper presents the general guidelines on developing a laboratory prototype Voltage Source Converter (VSC). One of the main possible reasons behind the limited hardware verification by postgraduate students, carrying out research in the area of power electronics and especially the VSCs, is the lack of knowledge and unavailability of proper tutorials and guidelines for developing hardware prototypes. In this paper, majorityof the auxiliary circuits and modules which are required for building up a prototype VSC are introduced. Proper examples are provided at each stage to improve the effectiveness of the developed guideline. The main difficulties of the hardware experiments are mentioned and possible solutions and recommendations are presented throughout the paper. It is believed that this paper will highly benefit the postgraduate students at the early stages of their hardware experiments.